The Influence of Risk Perception and Risky Riding Behavior on Motorcycle Accident Involvement among Young Riders in Surabaya - Santosa, Dimas Puji; Mayuni, Siti; Sugasta, Hervian Handika; Adibah, Fairuz; Saputra, Doddy Cahyadi (Fakultas Teknik Universitas Tanjungpura, 2026)
Motorcycle accidents remain a serious road-safety problem in developing countries, particularly among young riders who often exhibit risky riding behaviors. Risk perception is considered an important factor influencing such behaviors and accident involvement; however, the relationships among these variables remain poorly understood. This study aims to examine the relationships among risk perception, risky riding behavior, and accident involvement among young motorcycle riders. A quantitative approach was employed, using primary data collected via structured questionnaires distributed to young motorcycle riders, yielding 368 valid responses. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM), including evaluation of the measurement and structural models. The results indicate that risk perception has a significant negative effect on traffic errors (p = 0.010), speeding violations (p = 0.025), traffic violations (p = 0.002), and safety violations (p = 0.002), but has no significant effect on control errors and dangerous actions. Furthermore, traffic errors, speeding violations, and control errors significantly increase the risk of accidents. These findings suggest that improving risk perception can reduce risky riding behavior and contribute to motorcycle accident prevention efforts.